Adult Protective Services Training: Insights from California Caseworkers. Issue 3 (3rd April 2021) - Liu, Pi-Ju; Neumann, Alicia; Radcliffe, Kate; Chodos, Anna
ABSTRACT: Adult Protective Services (APS) training is critical to the mission of APS in supporting the workforce, but not much is known from caseworkers' perspectives. To learn more, 63 caseworkers in five California counties, from urban, suburban, and rural areas, participated in focus groups. Discussion was organized around three open-ended questions regarding implementation of the National Adult Protective Services Association (NAPSA) training content in practice: (1) What trainings have changed your practice and how? (2) How could training be changed to make it easier to implement? (3) What characteristics of your work environment interfere with implementation of learning? Through iterative reading and review of focus group transcripts, four themes emerged: (1) motivations, (2) barriers, (3) facilitators, and (4) impact. Caseworkers also made recommendations to improve training for better implementation of concepts and skills. Caseworkers involved in this study were quick to assert the need for increased access to training, more sophisticated content, and experiential learning. Moreover, expanding and enhancing safety training was recommended, as was aligning training with local needs and policies. Since the NAPSA approved APS core competencies and advanced topics are also offered and used in other counties and states, considering how to improve training could benefit caseworkers nationwide.